2022
DOI: 10.35848/1347-4065/ac9ac0
|View full text |Cite
|
Sign up to set email alerts
|

Long wavelength red to green emissions from {11 2¯ 2} semipolar multi-quantum wells on fully relaxed InGaN underlayer

Abstract: In this study, we report a high In composition {11-22} InGaN underlayer grown on an m-plane sapphire substrate and the multi-quantum wells (MQWs) grown on it. The InGaN template with high In composition (In:~18%) was fully relaxed. The MQWs photoluminescence (PL) spectrum on the InGaN underlayer exhibited a higher emission intensity and a longer emission wavelength compared with that on a GaN template. Additionally, when the InGaN underlayer was adopted, an InGaN barrier was more suitable than a GaN barrier fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The three samples showed almost the same surface morphologies with streak‐shape lines parallel to the [ 1 ¯ 1 ¯ 23 ] direction, which probably represent the surface morphology of the underlying semipolar GaInN layer. [ 23 ] The lower images in Figure 2 are surface morphologies obtained by the AFM observation for the same samples as in the upper images, in which their root‐mean‐square (RMS) roughness values are also shown. The results showed that a granular morphology was formed for all the samples and that their RMS values were as relatively small as less than 1.5 nm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The three samples showed almost the same surface morphologies with streak‐shape lines parallel to the [ 1 ¯ 1 ¯ 23 ] direction, which probably represent the surface morphology of the underlying semipolar GaInN layer. [ 23 ] The lower images in Figure 2 are surface morphologies obtained by the AFM observation for the same samples as in the upper images, in which their root‐mean‐square (RMS) roughness values are also shown. The results showed that a granular morphology was formed for all the samples and that their RMS values were as relatively small as less than 1.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 schematically shows a typical sample structure investigated in this study. The AlInN layers were grown on a semipolar { 11 2 ¯ 2 } GaInN template [ 23 ] using a horizontal‐type MOCVD system (Taiyo Nippon Sanso, SR‐2000). The semipolar GaInN template consisted of a 1.6 μm‐thick GaInN layer and a 1.4 μm‐thick GaN layer on an m ‐plane sapphire substrate, which was prepared via another MOCVD process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations